Increasing Secondary School Students' Creativity in Writing Skills: An Action Research - Bhandari, Bhim Lal (Butwal Campus Journal, 2024)
Creative writing is one of the most significant and challenging skills for students to master and improve their writing skills in English. This action research aims to implement action plans in English classes to help students increase their creativity in writing. The study used action research as its design, with action learning theory serving as the framework for guiding the research. I employed observation and self-reflective notes as research instruments. Since it is action research, it was conducted by considering it practitioner research to improve my classroom practice. Forty students of grade 12 from the academic year 2022/023 were selected as the participants of the study. This took place through planning, implementation, observations, data gathering and reflection. It presents different writing activities for developing creativity in writing skills as an action plan. Information was gathered through observations as the students participated in creative writing activities. The behaviour of students was observed during their engagement in creative writing activities. The result of this action research reveals that writing stories and diaries, journals, biographies, reflection and engagement in group work tasks enhance their creativity in writing skills.